Al-modified environmental barrier coatings for protection against water vapor corrosion. (June 2023) - Zhuo, Xueshi; Wang, Chao; Wang, Meng; Wu, Jian; Zhang, Xiaofeng; Cui, Jianlei; Mei, Xuesong; Fan, Zhengjie
Abstract: High-temperature water vapor corrosion is a great challenge for long lifetime of Si/mullite/Yb2 SiO5 Environmental Barrier Coatings. In this work, the Yb3 Al5 O12 modified layer was in-situ synthesized on the surface of Yb2 SiO5 layer to improve the steam resistance. The reaction mechanism of the Al-modified layer was explored. The steam corrosion experimental results indicated that the defects in Yb2 SiO5 layer healed, and the oxidation rate of Si-bonded coating was slowed down under the protection of modified layer. Additionally, the calculation results of first-principle molecular dynamics confirmed that Yb3 Al5 O12 has excellent steam corrosion resistance. Graphical Abstract: ga1 Highlights: A protective layer was prepared on the surface of the Yb2 SiO5 coating through the Al-modification method. The reaction of Yb3 Al5 O12 with water vapor needs to break through a higher energy barrier than that of Yb2 O3 and Yb2 SiO5 at 1400 ℃. The Al-modified EBCs exhibited excellent water vapor corrosion resistance due to the formation of a new Yb3 Al5 O12 phase as well as the healing of voids and microcracks in the Yb2 SiO5 coating.